Life cycle approach to health service delivery the Bataraza experiment - Aguirre, Angela Desiree M.; Veneracion, Cynthia Catacutan; Trinidad, Gracia V. (Quezon City Institute of Philippine Culture, Ateneo de Manila University, 1999)
"In 1997, the municipality of Bataraza in Palawan was chosen as the site of the pilot implementation of the life cycle approach (LCA) to health service delivery. Supported by the Women's Health and Safe Motherhood Project (WHSMP) of the Department of Health (DOH), the LCA pilot is a part of the search for field-level strategies which will ensure the immediate delivery of critically needed health services to vulnerable individuals, groups, and communities. It was implemented in 13 barangays of the municipality and involved community residents and groups, local government units (LGUs), the DOH, nongovernment organizations (NGOs), and other resource organizations and individuals. Based on a process documentation research undertaken on the LCA project, this volume describes the events and activities related to the LCA pilot implementation--which officially ended in June 1999--and the manner in which these were carried out. It likewise discusses the major issues and concerns which emerged during or were highlighted by the pilot implementation."--Chapter 1.
1. Life cycle approach pilot implementation : goals, participants, and setting -- 2. Preparing for the LCA Pilot : groundwork and related activities -- 3. Implementing the life cycle approach : activities and processes -- 4. Making the life cycle approach work : issues and concerns -- Appendices.
Keywords: Medical care -- Philippines -- Bataraza (Palawan) -- Case studies; Health services administration -- Philippines -- Bataraza (Palawan) -- Case studies; Public health administration -- Philippines -- Bataraza (Palawan) -- Case studies